Impact of Patient Age on Management of Hypothyroidism: A Survey of Physicians from Three Developing Regions - Beshyah, Salem A.; Bashir, Mohammed; Hafidh, Khadija; Afandi, Bachar; Shaikh, Shehla; Hammami, Sonia; Khalil, Ali B. (Journal of Diabetes and Endocrine Practice, 2024)
Background The thyroid-stimulating hormone (TSH) levels increase with age, and aiming for the same TSH target applicable in a younger population in older patients who are on replacement with thyroid hormones.Methods We assessed practice patterns regarding TSH goals and explored factors influencing physicians' decision-making when managing hypothyroidism. Multiple-choice questions in a case-based survey of a convenience sample of physicians practicing in relevant disciplines in three developing regions.Results Of the total 286, senior physicians represented 63% and mid-grades represented 27% of the respondents. Forty-one percent were endocrinologists, 19% were internists with endocrine interests, and 16% were family physicians. Over half (52%) practiced at a tertiary level and 42% had been in practice for over 20 years. Fifty percent of respondents had more than 20% of their patients over 65 years.Several attributes were factored into decision-making when managing hypothyroidism. Respondents took into account age (75%), preceded by the presence of cardiac arrhythmias (80%), pregnancy (79%), heart disease (78%), and patient symptoms (77%) when determining the treatment strategy. When presented with scenarios differing in patients' age, around 90% of physicians targeted a TSH ≤ 3.0 mIU/L in 30-year-old patients. Fifteen percent of respondents targeted a TSH of 1.6 to 3.0 mIU/L in octogenarians, but 78% targeted a TSH > 3.1 to 5.0 mIU/L in this group. Regardless of sex, physician-reported TSH goal ranges (0.1–0.5, 0.6–1.5, 1.6–3.0, and 3.1–5.0 mIU/L) increased directly to patient age. Overall, respondents were less inclined to start treatment in 85-year-olds than in 70-year-old females with TSH of 6 mU/L (20% vs. 11%). Females with a TSH of 15 mU/L were more likely to get treated than those with a 6 mU/L TSH. Vital persons are more likely to be treated with thyroxine than vulnerable persons for the same TSH levels. Multivariate analysis showed that compared with endocrinologists, family physicians and other specialties were less likely to consider age in their clinical decisions, odds ratio (OR) 0.2 (95% confidence interval [CI] 0.1–0.7), p = 0.018, and OR 0.3 (95% CI 0.1–0.8), p = 0.013, respectively.Conclusion A consensus is needed on the role of patients' age in hypothyroidism management, the complexity of managing hypothyroidism in an older adult patient, and the variability in practice patterns among physicians. Addressing these challenges demands ongoing dialogue and collaboration among health care providers to improve patient care and outcomes in hypothyroidism management across different age groups.
Keywords: older adults; hypothyroidism; survey; thyroid hormone therapy; overtreatment; age